Reading to learn in the content areas - Richardson, Judy S.; Morgan, Raymond F.; Fleener, Charlene E. (Wadsworth Cengage Learning, 2012)
The text explores how the increased availability of computers, instructional software, and Internet resources, as well as the rise of electronic literacy in general, have affected the ways children learn and create meaning from their world.